2014
DOI: 10.1016/j.jacc.2014.02.588
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Risk Profiling of Implanted Defibrillator Shocks With Circulating SCN5A mRNA Splicing Variants

Abstract: Objectives The aim of this study was to determine the association of SCN5A cardiac sodium (Na+) channel mRNA splice variants in white blood cells (WBCs) with risk of arrhythmias in heart failure (HF). Background HF is associated with upregulation of two cardiac SCN5A mRNA splice variants. that encode prematurely truncated, nonfunctional Na+ channels. Since circulating WBCs demonstrate similar SCN5A splicing patterns, we hypothesized that these WBC-derived splice variants might further stratify HF patients at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 29 publications
1
11
0
Order By: Relevance
“…This dominant negative effect is mediated by the UPR 1 . Here, we were able to show that heart tissue from patients with HCM showed a decreased full-length SCN5A mRNA transcript abundance and increased abundances of abnormal SCN5A mRNA splice variants, similar to the previous results in other forms of cardiomyopathy 1, 2, 12 . This abnormal SCN5A mRNA splicing was accompanied by elevations in the splicing factors Luc7a and RBM25 which are known to cause abnormal SCN5A mRNA splicing 2 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This dominant negative effect is mediated by the UPR 1 . Here, we were able to show that heart tissue from patients with HCM showed a decreased full-length SCN5A mRNA transcript abundance and increased abundances of abnormal SCN5A mRNA splice variants, similar to the previous results in other forms of cardiomyopathy 1, 2, 12 . This abnormal SCN5A mRNA splicing was accompanied by elevations in the splicing factors Luc7a and RBM25 which are known to cause abnormal SCN5A mRNA splicing 2 .…”
Section: Discussionsupporting
confidence: 90%
“…Previously, we have shown that ischemic and nonischemic heart failure are associated with increased abnormal SCN5A mRNA splicing, that the expression of SCN5A cardiac Na + channel mRNA splice variants in white blood cells (WBCs) correlates with levels in the heart, and that normalized WBC splicing levels predict increased risk of ventricular arrhythmias 12 . In dilated or ischemic cardiomyopathy, the two SCN5A mRNA splicing variants reach greater that >50% of the total SCN5A mRNA and do not produce functional Na + channels 2, 5 .…”
Section: Discussionmentioning
confidence: 99%
“…45 Interestingly, aberrant SCN5A splicing is also observed in peripheral blood cells from patients with heart failure and is tightly correlated with myocardial SCN5A mRNA levels, thus providing a peripheral blood "window" into the electric properties of the heart. 46 Peripheral blood SCN5A expression profiling with PCR predicted appropriate ICD shock therapy in patients with heart failure with high accuracy. 46 These early data lay the foundation for a novel gene expression-based biomarker to help risk-stratify patients for ICD therapy.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 99%
“…46 Peripheral blood SCN5A expression profiling with PCR predicted appropriate ICD shock therapy in patients with heart failure with high accuracy. 46 These early data lay the foundation for a novel gene expression-based biomarker to help risk-stratify patients for ICD therapy.…”
Section: Musunuru Et Al Expressed Genome In Cardiovascular Diseases Amentioning
confidence: 99%
“…It has also been shown that miRNA expression changes in response to treatment of heart failure including well-established medical therapies as well as advanced therapies such as mechanical unloading with left ventricular assist devices [94], and, promisingly, miRNA-targeted therapies [97]. Patients who respond to cardiac resynchronization therapy have been shown to have different miRNA profiles compared to patients who do not [98], and differences in cardiac sodium channel mRNA splice variants have been shown to increase risk for arrhythmia as measured by implantable cardioverter-defibrillator (ICD) events in patients with CHF [99]. Another analysis of tissue from endomyocardial biopsies identified a group of overexpressed genes which predicted prognosis in patients with new-onset heart failure [100].…”
Section: Determining Prognosis For Patients With Cad and MImentioning
confidence: 99%